Stateful DBA Hypervisor Supporting SLAs with Low Latency & High Availability in Shared PON - Ruffini, Marco (My University, 2021)
We present a stateful DBA hypervisor for shared PONs capable of meeting specific flow-level service level agreements, supporting services requiring strict latency and high availability. We report considerable improvement compared to standard stateless priority-based mechanisms.
Optical Fibre Communications (OFC)
PUBLISHED
Keywords: Passive Optical Networks; Quality of Service; Service level agreements